Assessment of lateral to medial dissection of Calot’s triangle in laparoscopic cholecystectomy: A case-control study - Aydın, Oğuz Uğur; Tihan, Necdet Deniz; Sabuncuoğlu, Mehmet Zafer; Dandin, Özgür; Yeğen, Fatih Serkan; Balta, Ahmet Ziya; Karakaş, Dursun Özgür (Journal of Surgery and Medicine, 2018)
Aim: We aimed was to compare intraoperative results of the dissection of the Calot’s triangle through classical method and the dissection starting from the posterior side of the cystic duct toward the cystic artery along lateral to the medial surface in LC. Methods: In Group 1 (n=60), peritoneum was dissected anteriorly along medial to the lateral surface of the Hartmann’s pouch. In Group 2 (n=60), the peritoneal dissection started from the posterior side of the cystic duct toward the cystic artery along lateral to the medial surface of the Hartmann’s pouch. Data including demographic characteristics of the patients, cystic duct dissection time, cystic artery dissection time, and intraoperative bleeding amount were recorded. Results: The median cystic duct and cystic artery dissection times were 308.00 (IQR=68-927) sec and 403.50 (IQR=98-1045) sec, respectively. In Group 1, these values were 347.90±186.33 and 469.73±225.02 sec for cystic duct and cystic artery dissection, respectively. In Group 2, the median cystic duct and cystic artery dissection times were 285.50 (IQR=68-927) sec and 389.50±143.28 sec, respectively. There was no statistically significant difference in the Calot’s triangle dissection time (p=0.122 and p=0.075, respectively) and intraoperative blood loss amount between the groups (p=0.852). Conclusions: Our study results suggest that this technique can be safely performed in an acceptable time in LC patients. It also appears to be a safe alternative option for residents, left-handed surgeons, and patients with biliary and vascular abnormalities.